Some Anthropometric Measurements and Their Relationship With Lunges and Pulse Absolute Vital Capacity Before and After Effort In Football - Majeed, Omer (Journal of Physical Education, 2017)
The problem of the research lies in answering the following questions; does lunges vital capacity related to heart pulse? Is heart pulse related to some anthropometric measurements according to energy systems? The aim of the research is to identifying the anthropometric measurements, lunges vital capacity and heart rate during effort according to working energy systems in footballers as well as finding the relationship between absolute vital capacity and heart pulse before and after effort according to energy systems of footballers. The researcher used the descriptive method. The subjects were (27) advance football players from Erbil club then (16) players only were included in this research. The researcher used electronic stopwatch to measure time, scales for mass and measuring tape for measuring the height and girth. Sprometer was used for measuring lungs capacity and stethoscope for measuring heart pulse. 100m dash test was conducted as a test. The subjects were tested before and after the tests then the data was collected and treated using simple correlation and standard deviation to come up with the results.The researcher concluded that there is a high significant correlation between anthropometric measurements used in the research as well as significant correlation between vital capacity during and after 100m running for 4 and 5 minutes. There were no significant correlations between vital capacity, heart pulse and anthropometric measuring. The researcher recommended paying attention to respiratory system physiology and making regular tests on players according to their energy systems to find the relationship between capacity, heart pulse and anthropometric measurements.